Aggressiveness and mycotoxin profile of Fusarium avenaceum isolates causing Fusarium seedling blight and Fusarium head blight in UK malting barley - Inbaia, Safieddin; Farooqi, Arifa; Ray, Rumiana V. (Frontiers in Plant Science, 2023)
Fusarium avenaceum causing Fusarium seedling blight (FSB) and Fusarium head blight (FHB) on barley is associated with economic losses of crop yield and quality, and the accumulation of mycotoxins including the enniatins (ENNs A, A1, B and B1). Although F. avenaceum is the main producer of ENNs, studies on the ability of isolates to cause severe Fusarium diseases or produce mycotoxins in barley are limited. In this work, we investigated the aggressiveness of nine isolates of F. avenaceum to two cultivars of malting barley, Moonshine and Quench, and defined their ENN mycotoxin profiles in in vitro and in planta experiments. We assessed and compared the severity of FSB and FHB caused by these isolates to disease severity by F. graminearum, F. tricinctum and F. poae. Quantitative real-time polymerase chain reaction and Liquid Chromatography Tandem Mass Spectrometry assays were used to quantify pathogen DNA and mycotoxin accumulation, respectively, in barley heads. Results showed that isolates of F. avenaceum were equally aggressive to barley stems and heads and caused the most severe FSB symptoms resulting in up to 55% reductions of stem and root length. Fusarium graminearum caused the most severe FHB disease, followed by the isolates of F. avenaceum with the most aggressive F. avenaceum isolates capable of causing similar bleaching of barley heads as F. graminearum. Fusarium avenaceum isolates produced ENN B as the predominant mycotoxin, followed by ENN B1 and A1 in vitro. However, only the most aggressive isolates produced ENN A1 in planta and none produced ENN A or BEA either in planta or in vitro. The capacity of F. avenaceum isolates to produce ENNs was related to the accumulation of pathogen DNA in barley heads, whilst the synthesis and accumulation of ENN A1 in planta was related to FHB severity. Cv. Moonshine was significantly more resistant, than Quench, to FSB or FHB, caused by any Fusarium isolate, and to the accumulation of pathogen DNA, ENNs and BEA. In conclusion, aggressive F. avenaceum isolates are potent ENN producers causing severe FSB and FHB with ENN A1 requiring further investigation as potential virulence factor for F. avenaceum in cereals.